Influence of mineral fertilizers on the content of basic macro elements in soil and two years plants of apple sivers forest crops created by seedlings with a closed root system - Khujaniyazovich Mamutov Bakhrom; Aleeksandrovich Butkov Yevgeniy; Ismailovich Ruzmetov Umid; Khudoynazar Ugli Ulugov Chorshanbi; Fayzullayevna Ulugova Safargul; Gulmurzaevich Temirov Jamshid (BIO Web of Conferences)
The article presents the results of research into the physical and mechanical properties of soils and fertilizers, the effectiveness of the method of applying mineral fertilizers layer by layer on the formed dams, the development of the design of machines for the formation and fertilization of furrows, as well as the justification of the technological processes of their operation.